Effectiveness of Parents’ Workshop on Home-School Partnership and Students’ Mathematics Performance. The Case of a Public Secondary school in Botswana (International Journal of Scientific Research and Management (IJSRM), 2022)
It is undisputable that an effective home-school partnership has an impact on their children’s learning and subsequent academic performance. However, the extent of parental involvement is found to be lacking due to various reasons according to the literature. This paper reports on the effectiveness of utilizing workshops as an intervention strategy to facilitate a home-school partnership that could enhance student mathematics performance in a public senior secondary school in Botswana. Parents from one, purposively selected public senior secondary school, participated in this study. The study used a pragmatist paradigm to draw on a mixed-methods approach and employ a quasi-experimental research design with experimental and control groups. Questionnaires for parents and their children, parents’ interviews, and tests in mathematics were the main data collection instruments for this study and were used as pre and post-interventions. The parents’ workshops intervention was implemented for a period of three weeks on the experimental group. Parents were provided with knowledge and skills through presentations on parental involvement. The results demonstrated that the parents’ workshops intervention improved home-school partnership. The results showed that the intervention had a large positive impact on Home-school communication with an effect size difference of 2.260 between pre-test and post-test mean scores for the parents in the experimental group. Consequently, children’s mathematics performance positively changed after the intervention. The difference between pre-test and post-test within the control group showed a small effect size (0.308) while a large and practical effect size (2.215) was found between pre-test and post-test within the experimental students.